Rules of Law in the Implementation of Indonesia Armed Forces Authority to Overcome Terrorism in Indonesia - ARIEF FAHMI LUBIS (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Terrorism is one of the threats and disturbances facing Indonesia in the future, in the last few years its activities have increased, so that it has an effect on efforts to realize national goals as formulated in the fourth paragraph of the Preamble to the 1945 Constitution. In this case the involvement of the TNI to assist the Police is very much needed. However, not all parties, such as government agencies and the DPR, agree with this because the act of eradicating terrorism for the TNI has its own obligations and creates juridical problems in its implementation. The involvement of the TNI in dealing with acts of terrorism will pose a serious threat to the dynamics of democracy, human rights and the rule of law in Indonesia. A study of the implementation of the TNI’s authority through literature studies in order to obtain materials and information needed in accordance with the subject matter: primary legal materials, secondary legal materials. Through interviews by using guidelines/guide questions so as not to deviate from the problems being studied. Followed by analyzing the data qualitatively described using systematic words. The approach used in this study uses a statutory approach. From the problems above and the method used, it can be concluded that it can provide benefits for the development of legal science and the field of administrative law, as a material for consideration in the formation of legislation related to the TNI’s authority in dealing with acts of terrorism.